Canine gastrointestinal pythiosis: a case report in Brazilian Pantanal from a diagnostic approach - Aguiar, Daniel Moura de; Sifuentes, Manoela; Magalhães, Aline; Pereira, Nathalia; Pescador, Caroline; Cândido, Stéfano; Dutra, Valéria; Nakazato, Luciano; Barreto, Uiara; Burema, Mayara; Néspoli, Pedro; Rodrigues, Juliana (Brazilian Journal of Veterinary Research and Animal Science, 2022)
Pythiosis is caused by an aquatic fungus-like organism (Pythium insidiosum). It is considered an important public health issue as it can affect both animals and humans. This paper reports a case of gastrointestinal pythiosis in a dog. The patient was hospitalized for four days, during which the animal received supportive and symptomatic treatment. But the applied treatment was unsuccessful and the dog’s clinical condition worsened, culminating in death. Complementary imaging tests such as radiography and ultrasonography, as well as hematological tests, were performed during the hospitalization period. The definitive diagnosis was reached in the postmortem as macroscopic and microscopic characteristics suggested the presence of intestinal granuloma and accentuated multifocal suppurative necrotic enteritis. Additionally, the histological evaluation revealed morphological structures compatible with P. insidiosum. Also, the results of nested PCR performedshowed partial amplification (105 bp) of the ITS1 region of the ribosomal gene of P. insidiosum.